2021
DOI: 10.1111/1759-7714.14150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circ_0058357 as a regulator in non‐small cell lung cancer cells resistant to cisplatin by miR‐361‐3p/ABCC1 axis

Abstract: Background Drug resistance is a major clinical drawback behind the failure of chemotherapy in non‐small cell lung cancer (NSCLC). In this study, we undertook to identify the precise role of circular RNA (circRNA) circ_0058357 in the functional properties of DDP‐resistant NSCLC cells. Methods Circ_0058357, miR‐361‐3p and ATP‐binding cassette (ABC) subfamily C member 1 (ABCC1) were quantified by qRT‐PCR and western blot. Cell survival and viability were gauged by MTT assay. Cell proliferation, apoptosis, invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The EdU experiment was operated according to the instructions of the EdU Apollo488/567 in vitro kit (Solarbio) as reported [ 27 ]. Briefly, transfected H1299/Taxol and A549/Taxol cells (4,000 cells/well) were seeded in 96-well dishes for 48 h, treated with 50 nM of EdU reagent for 2 h, and then dyed with 1× Apollo488/567 for 30 min, followed by the nucleus staining with 4’,6-diamidino-2-phenylindole (DAPI, Solarbio) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EdU experiment was operated according to the instructions of the EdU Apollo488/567 in vitro kit (Solarbio) as reported [ 27 ]. Briefly, transfected H1299/Taxol and A549/Taxol cells (4,000 cells/well) were seeded in 96-well dishes for 48 h, treated with 50 nM of EdU reagent for 2 h, and then dyed with 1× Apollo488/567 for 30 min, followed by the nucleus staining with 4’,6-diamidino-2-phenylindole (DAPI, Solarbio) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…After transfection, ~1,000,000 H1299/Taxol and A549/Taxol cells were harvested and stained in accordance with the Annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) apoptosis detection kit (Solarbio) specifications as described elsewhere [ 27 ]. A total of 100,000 events were analyzed by Cytoflex flow cytometry (BECKMAN COULTER, Pasadena, Texas, USA), and the apoptotic cells were defined as the cells that was positive with Annexin V.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, circ‐PIP5K1A could sponge miR‐101, promoted the increased expression of ABCC1, and then regulated the progression and cisplatin sensitivity of NSCLC 51 . Furthermore, the expression of ABCC1 and cisplatin sensitivity were also regulated by circ‐PVT1 in lung adenocarcinoma 52 and by circ_0058357 in NSCLC 53 . In addition, Liang et al reported that circRNA_103615 promoted ABCB1 expression and the cisplatin resistance of NSCLC 54 .…”
Section: Circular Rnas and Drug Resistance Of Lung Cancermentioning
confidence: 99%
“…For instance, hsa-miR-98-5p inhibits the expression of copper transporter 1 (CTR1) to reverse CP resistance in NSCLC [ 55 ]. By targeting the miR-361-3p/ABCC1 axis, circ0058357 inhibition reduces the proliferation and metastasis of NSCLC cells and partially sensitizes them to CP [ 56 ]. In addition, miR-1914-3p can also reverse chemoresistance by regulating yes-associated protein (YAP) [ 57 ].…”
Section: Mirnas As Complementary Therapiesmentioning
confidence: 99%